2014
DOI: 10.1177/070674371405900107
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Informant Agreement of Child, Parent, and Teacher Ratings of Child Anxiety within Community Samples

Abstract: Correlations between parent and teacher with child ratings were poor over 3 time points, and significant differences were found for sex and grade. Research is needed to understand reasons for poor concordance between parent, child, and teacher ratings of anxiety for all children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 16 publications
6
27
0
2
Order By: Relevance
“…Our results are consistent with previous studies that suggested teachers have only modest sensitivity to children's internalizing symptoms, where teachers have been prompted with standardized scales (Achenbach, McConaughy, & Howell, ; Miller, Martinez, Shumka, & Baker, ), or hypothetical vignettes (Loades & Mastroyannopoulou, ). Additionally, by asking teachers to rate all their pupils, we were able to establish that the children teachers perceived as experiencing the lowest levels of anxiety did indeed report fewer symptoms than their peers, whereas children perceived to be in the middle range reported similar levels of symptoms to those thought to be the most anxious.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with previous studies that suggested teachers have only modest sensitivity to children's internalizing symptoms, where teachers have been prompted with standardized scales (Achenbach, McConaughy, & Howell, ; Miller, Martinez, Shumka, & Baker, ), or hypothetical vignettes (Loades & Mastroyannopoulou, ). Additionally, by asking teachers to rate all their pupils, we were able to establish that the children teachers perceived as experiencing the lowest levels of anxiety did indeed report fewer symptoms than their peers, whereas children perceived to be in the middle range reported similar levels of symptoms to those thought to be the most anxious.…”
Section: Discussionsupporting
confidence: 91%
“…It has however to be pointed out that the observed relation between anxiety and the other constructs of interest was limited to the measure of general anxiety, and more precisely to the teachers' proxy report of children's anxiety. This pattern of results is consistent with previous studies, in which the agreement between children's self-reports and the proxy reports of general anxiety from either parents' (e.g., [78,114]) or teachers' (e.g., [7,78]) was commonly quite low (see the recent metaanalysis by [22]). Teachers' capacity to detect the anxiety symptoms, when present, was repeatedly demonstrated (e.g., [58,68,79,101]), and the discrepancy with children's self-ratings was hypothesized to depend on the children's difficulty to appraise a multifaceted and complex construct such as general anxiety is.…”
Section: Independent Effects Of Cognitive and Affective Components Onsupporting
confidence: 91%
“…Though the ADIS/ASA incorporates clinical judgment, clinicians were constrained in their judgments to information provided by the parent in this study. Self and teacher reports of internalizing symptoms, like anxiety, often differ in youth with (Blakeley-Smith, Reaven, Ridge, & Hepburn, 2012;Kaat & Lecavalier, 2015) and without ASD (Miller, Martinez, Shumka, & Baker, 2014), and these differences in perspective may provide important, complementary insights regarding the expression and pervasiveness of a child's symptoms (De Los Reyes & Kazdin, 2005). Future studies should examine differences in the prevalence of symptoms based on parent, child and composite (diagnoses endorsed by parent or child) reports and also what mental age and verbal abilities may be required for various child and parent report measures to be useful.…”
Section: Limitationsmentioning
confidence: 99%